If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(b + 4) = -24 + 6b Reorder the terms: 5(4 + b) = -24 + 6b (4 * 5 + b * 5) = -24 + 6b (20 + 5b) = -24 + 6b Solving 20 + 5b = -24 + 6b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-6b' to each side of the equation. 20 + 5b + -6b = -24 + 6b + -6b Combine like terms: 5b + -6b = -1b 20 + -1b = -24 + 6b + -6b Combine like terms: 6b + -6b = 0 20 + -1b = -24 + 0 20 + -1b = -24 Add '-20' to each side of the equation. 20 + -20 + -1b = -24 + -20 Combine like terms: 20 + -20 = 0 0 + -1b = -24 + -20 -1b = -24 + -20 Combine like terms: -24 + -20 = -44 -1b = -44 Divide each side by '-1'. b = 44 Simplifying b = 44
| 600=(x+0)(x+1) | | 3n^2+8n-40=0 | | 3x+4x+5=180 | | 4(x+1)=3(x-2) | | 8x-1+3=66 | | 78-5x=9x-22 | | 3x+8=5x-6(x+4) | | 7n-1=-(-8n+3) | | 3h+11=17+5h | | 1.2q-1.5-4.7q=-4.5q-4.5 | | 0.5(3x+5)-0.1(12x-5)=3(1+0.1x) | | m^3-4m^2+5m-2=0 | | -8=2(x-5) | | x+17.8=-4.2 | | 2x+3(x-4)=2(2x-6)+x | | 5d+7e+3d-6e= | | -15.7-x=-8.3 | | (x+1)(x+2)(x+3)(x+4)=24 | | 9c+3d-4c+2d= | | 9.2-x=-13.4 | | 5a+2y-2a+3y= | | 8a-3a= | | x(x-3)2=80 | | -9x^2+10x-1=0 | | 13.5*x=20 | | 13.5-x=21.8 | | X^2=1-4X | | X^2-40=9 | | -9x*2+10x-1=0 | | xm+5x=m-2 | | -9x+10x-1=0 | | 5(3ax-8)=a(4x+7) |